(untitled) (BIRDEM Medical Journal, 2020)
Background: Thyroid hormones have profound effects on reproduction and pregnancy. A relationship betweenthe thyroid gland and the gonads is suggested by the far more frequent occurrence of thyroid disorders inwomen. Hormonal disorders of female reproductive system are comprised of a number of problems resultingfrom dysfunction of hypo-thalamic-pituitary ovarian axis. These relatively common disorders often lead toinfertility. Concomitant Diabetes and other metabolic abnormalities or endocrinopathy flare up the condition.This study was conducted to find out any difference in thyroid function among diabetic and non-diabeticpatient presenting with primary infertility. Methods: In this study total 174 patients were included and allocated into two groups, 87 in each group.Group I were diabetic infertile women and group II were non diabetic infertile women. Thyroid hormoneprofile were done and compared between groups. The data were based on the answers came from interviewsand medical records registered in the OPD follow up, investigation report, treatment paper and notes inhospital file sheet. Data processing work was consisted of registration schedules, editing computerization,preparation of dummy table, analyzing and matching of data. Results: No difference was observed in respect of demographic profile. It was observed that, majority ofpatients 73(41.9%) belonged to age 26-33 years, mean age was found 26.3±10.9 years in Group-I and 26.7±11.6years in Group-II. Low T3 was found in 15(17.2%) patients and in 9(10.3%) patients group I and group IIrespectively. Mean FT4 was found 8.25±1.5 pmol/L in group I and 10.57±1.82 pmol/L in group II. Raised TSHwas found in 23(26.4%) patients and 13(14.9%) patients in group I and group II respectively. On interpretationof thyroid function test, 71.8% (125/174) patients had normal finding or in euthyroid status (64.3% in group Iand 79.3% in group II). Present study shows that, frequency of thyroid dysfunction was common in group-Ipatients than group-II (35.6% vs. 20.6%). primary hypothyroidism was predominant abnormality, noted15(17.2%) patients in group I and 9(10.3%) patients in group II patients. Conclusion: Hypothyroidism is the most common thyroid dysfunction found in infertile females and it ispredominant in diabetic infertile group. Hence assessment of thyroid function should be considered as animportant component in infertility work up of women. Birdem Med J 2020; 10(2): 92-96